Informal caregiving: empowering social support programs by employers - Nur Saadah Mohamad Aun,; Rusyda Helma Mohd, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The problems faced by people providing informal care to family members with chronic illness has not been discussed thoroughly in Malaysia. This research has therefore been carried out with the aim of exploring types of informal social support currently practiced and related issues. It is based on a qualitative analysis of the interviews of five informal caregivers responsible for chronically ill family members in Kuala Lumpur. All respondents have struggled to provide the financial and emotional support required, especially as four were unemployed. These respondents were dependent on the family breadwinner, relatives and/or agencies for their daily needs, and also for the costs of medical treatment. They were physically able to work, but had chosen to focus on giving care instead. Some of the respondents had worked previously, but resigned after the condition of their care recipient had worsened. As a consequence, the respondents were facing financial hardship. Thus this analysis proposes that employers should incoporate social support programs into work contracts to enable better working hours and more flexibility for those staff engaged in informal care. By adopting this social support program, it is hoped that informal caregivers could have more financial independance and be less reliant on government agencies and families for financial assistance.